2017
DOI: 10.1124/dmd.117.076745
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Increases Norbuprenorphine Clearance in Mice by Induction of Hepatic Glucuronidation

Abstract: Norbuprenorphine (NBUP) is the major active metabolite of buprenorphine (BUP) that is commonly used to treat opiate addiction during pregnancy; it possesses 25% of BUP's analgesic activity and 10 times BUP's respiratory depression effect. To optimize BUP's dosing regimen during pregnancy with better efficacy and safety, it is important to understand how pregnancy affects NBUP disposition. In this study, we examined the pharmacokinetics of NBUP in pregnant and nonpregnant mice by administering the same amount o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 37 publications
3
9
0
Order By: Relevance
“…Mice were maintained under 12-h light/dark cycles, and food and water were provided ad libitum . Pregnant mice on gestation day (gd) 15 were obtained and maternal tissues (liver, kidney and brain) were collected as previously described [7, 14]. Gd 15 was selected as we previously showed that mRNA levels of most drug-metabolizing enzymes and transporters in the liver and kidney reached the maximal changes on gd 15 and remained relatively unchanged after gd 15 [10].…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Mice were maintained under 12-h light/dark cycles, and food and water were provided ad libitum . Pregnant mice on gestation day (gd) 15 were obtained and maternal tissues (liver, kidney and brain) were collected as previously described [7, 14]. Gd 15 was selected as we previously showed that mRNA levels of most drug-metabolizing enzymes and transporters in the liver and kidney reached the maximal changes on gd 15 and remained relatively unchanged after gd 15 [10].…”
Section: Methodsmentioning
confidence: 99%
“…Protein quantification of transporters in the liver, kidney and brain of pregnant and non-pregnant mice by quantitative LC-MS/MS proteomics analysis. Quantification of changes in protein levels of Abcb1a (a P-gp isoform), Abcb1b (a P-gp isoform), Abcg2 (Bcrp), Abcb11 (Bsep), Abcc2 (Mrp2), Abcc3 (Mrp3), Abcc4 (Mrp4), Slco1a1 (Oatp1a1), Slco1a4 (Oatp1a4), Slco2b1 (Oatp2b1) and Slc22a3 (Oct3) in the liver, kidney and brain (Table 1 ) of pregnant and non-pregnant mice was carried out using a surrogate peptide-based LC-MS/MS method as previously described [7, 14, 15]. Transporter protein was quantified by the surrogate peptide LC-MS/MS method (https://ascpt.onlinelibrary.wiley.com/doi/abs/10.1002/cpt.819).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations